The influence of strength training in jump horizontal and vertical levels to football adolescents goalkeepers - Gomes, Fabiano Vieira (2012)
This study aimed to evaluate the influence of strength training to the levels of horizontal and vertical thrust of the soccer goalkeeper field of the youth category. The procedures used to analyze the level of the bases were jumping plyometric (jumping). The study was carried outon the pitch, and used as a example two goalkeepers male aged between 15 and 16 year old from a soccers choolin the city of Ponta Grossa/PR, using only the body's own weight of each athlete to the development of training. The development of research and testing occurred during the training school. We assessed the evolution of levels of horizontal and vertical jumps of goalkeepers tested, it was concluded that the work force improves the goalkeepers jump forward to the significant gains made during the research.